“Earthly life continues, full of incredible labour...” Letters from metropolitan Elevferiy (Bogoyavlensky) of Lithuania and Vilna to metropolitan Sergius (Stragorodsky) - Andrey Kostryukov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The publication introduces into scientific circulation four letters from Metropolitan Eleutherius (Bogoyavlensky) of Lithuania and Vilna to the Deputy Patriarchal Locum Tenens Metropolitan Sergius (Stragorodsky). The letters are dated 1934. The author of the letters not only headed the Diocese of Lithuania, but also, from 1930, managed the few parishes of the Moscow Patriarchate in Western Europe. Metropolitan Eleutherius reported on important events and problems that arose in the parishes entrusted to him. One of them was the division at the Three Hierarchs Compound in Paris, caused by the wrong parish policy of Archbishop Benjamin (Fedchenkov). Another problem was the appointment of a new rector for the Three Saints Compound in Paris. For some time, the apologist of the Moscow Patriarchate I.A. Stratonov. Metropolitan Eleutherius reported on the situation in the Russian Church Abroad and on the patronage, she received from Patriarch Varnava of Serbia. The author of the letters considered his policy to be wrong and uncanonical. At the same time, the metropolitan spoke about the reconciliation between the head of the Russian Church Abroad, Metropolitan Anthony (Khrapovitsky) and the head of the Western European Russian Exarchate, Metropolitan Evlogy (Georgievsky). The letters reflect other events as well. Among them are the mission of Hieromonk Demetrius (Balfour) among the Anglicans, the last days of Archpriest Sergei Sokolovsky, a hero of the First World War who joined the Renovationist schism and converted to Catholicism, about the attempts of the publicist M.A. Kallash to publish a pamphlet against the Russian Church Abroad, etc. Many of Metropolitan Eleutherius' assessments are biased, but, on the whole, the letters are an important source on the history of Russian Orthodoxy in exile